Short-term outcomes of parastomal hernia surgical repair - Lazauskaitė, Deimantė; Paužas, Henrikas (Lietuvos chirurgija, 2025)
Background. Parastomal hernias are one of the most common complications after stoma formation surgeries. Although some parastomal hernias may be asymptomatic, most patients require surgical treatment, even though no established optimal surgical method exists. Objective – to review the outcomes of surgical treatment for parastomal hernia. Methods. A retrospective analysis of patients who underwent parastomal hernia repair at the Department of Surgery of the LSMU Kaunas Clinics between 2001 and 2023 was conducted. Age, gender, symptoms caused by parastomal hernia, type of stoma, the number of primary and recurrent hernias, the number of elective and emergency surgeries, open surgical methods, operation duration, hernia orifice size, complications and length of hospital stay were analysed. The impact of risk factors on complication rates was also evaluated. Statistical data analysis was performed using Microsoft Excel and SPSS (Statistical Package for the Social Sciences) version 29.0. Results. A total of 91 patient medical records were analysed. The mean age of patients was 68±12 years. Open surgical methods were parastomal hernia repair with mesh – 48 (52.8%) and with suture repair – 43 (47.3%). Postoperative recovery was uneventful in 52 (57.1%) patients, while 39 (42.9%) patients had complications. No statistically significant differences were found in complication rates between risk factors (p > 0.05). The average length of hospital stay was 9.7±7.4 days. Conclusions. A retrospective analysis of parastomal hernias conducted between 2001 and 2023 showed that the number of parastomal hernia repair with mesh increased annually. However, the use of suture repair remained a common surgical method. Assessing the impact of risk factors on complications, no statistically significant differences were found.
Keywords: parastomal hernia; treatment outcomes; mesh repair; suture repair; complications